Chemical Constituent from Alstonia Spathulata BL. (Apocynaceae) - Tee Chuan Thing, Ahmad Kartini, Awang Khalijah, Tan Siow Ping, Nafiah Mohd Azlan (N/A, 2012)
Chemical Constituent from Alstonia Spathulata BL. (Apocynaceae) by Tee Chuan Thing, Ahmad Kartini, Awang Khalijah, Tan Siow Ping, Nafiah Mohd Azlan,